Investigating Undergraduate Students' Viewing Behaviors of Academic Video in Formal and Informal Settings. Issue 4 (2nd October 2019) - Campbell, Laurie O.; Planinz, Tracey; Morris, Kelly; Truitt, Joshua
Abstract: The use of video is prevalent in both face-to-face and online classrooms. Online learning leverages the use of video to support and provide instruction through the visuals video affords. The following study documents how undergraduate students interacted with video both in online and face-to-face environments and includes their video-watching preferences. Participants provided context as to how they engage with assigned video outside of the face-to-face classroom. Participants confirmed that they rarely watched video in a linear manner when the video was over five minutes. When watching longer video, they skipped through the video, watching it in a non-linear fashion. These higher education students indicated that they were more attentive to portions of video when instructors incorporated video annotations in the online environment. Further, the results suggested that students tend to re-watch video when instructors embedded knowledge-check questions. The insights from the study informs promising practices when incorporating video in instruction for teaching and learning in all modes of instruction (flipped, face to face, hybrid, and online).